Hula as a physical activity and social support intervention for sustained activity in female breast and gynecologic cancer survivors - Bantum, Erin O.; Yamada, Paulette M.; Makolo, TeMoana; Yu, Herbert; Pagano, Ian; Subia, Natalie; Walsh, Catherine; Loo, Lenora W. M. (Frontiers in Psychology, 2023)
Background Physical activity improves health and psychosocial functioning for people who have been diagnosed with cancer. Native Hawaiians face disparities for some cancers, including breast cancer. Delivering culturally grounded interventions has the potential to improve enjoyment and adherence to the intervention. We sought to test the adherence and impact of a 6 month randomized wait-list controlled trial of hula. Methods In this randomized wait-list controlled design people who had been diagnosed with breast or gynecologic cancers were invited to participate with other cancer survivors in a group based setting. Participants were randomized to begin hula immediately or after six months. Attendance was collected and heart-rate measured three times per session. In addition, demographic data, self-report psychosocial data, and biological data (findings will be reported elsewhere) were collected at three time points: baseline, 6 months, and 12 months. The study included six months of hula, twice per week, 60 min each session. In addition, participants committed to practice 60 min per week at home. Results Participants in the study (n = 42) attended, on average, 72% of the sessions. Significant increase in moderate physical activity (d = 0.50, p = 0.03) was observed in the intervention versus control group. For the measures of intra-individual changes pre-and post-intervention, an increase in total physical activity were seen in the intervention group (d = 0.69, p = 0.003), daily caloric intake decreased (d = −0.62, p = 0.007), and a reduction in waist circumference (d = −0.89, p = 0.0002) that was sustained six months after completion of the intervention. Psychosocially, cognitive functioning significantly declined from baseline to 12 months (d = −0.50, p = 0.03), with role functioning improving (d = 0.55, p = 0.02), social constraints increasing (d = 0.49, p = 0.03), and financial difficulties improving (d = −0.55, p = 0.02). Conclusion Sustainable physical activity is crucial to improve both the survival and quality of life of cancer survivors. Culturally grounded interventions, such as hula have the potential to increase the maintenance of physical activity. In addition, they create a support group where the benefits of people who have all experienced cancer can gather and garner those benefits of social support, too. This study was registered as a clinical trial through the National Cancer Institute (NCT02351479). Clinical trial registration Clinicaltrails.gov, NCT02351479.